The effect of environmental poultry samples on the pH of typical Salmonella pre-enrichment and enrichment media following incubation. (5th October 2017) - Cox, N A; Cosby, D E; Berrang, M E; Richardson, K E; Holcombe, N; Weller, C
Abstract: The first step to detect Salmonella in feed and other dry contaminated samples is a pre-enrichment broth that can assist in the recovery of small numbers of stressed Salmonella cells. A previous study demonstrated that incubation of feed and feed ingredients in commonly used pre-enrichment media resulted in a low pH that injured or killed the Salmonella . The objective of this study was to determine which environmental samples and pre-enrichment and selective broths could interfere with the accuracy of Salmonella detection by allowing pH to drop. Samples were collected from commercial poultry operations. Triplicate 10-g subunits were dispensed into sterile 18-oz Whirl Pak bags and 90 mL of each of the media [lactose broth (LB), buffered peptone water (BPW), Universal Pre-enrichment (UP), minimal salts (M-9), tetrathionate broth (TT) and Rappaport-Vassiliadis broth (RV)] were added to the bags and incubated 24 h at 37°C (or 42°C for RV and TT). The pH was measured after incubation. With turkey litter, fluff, and eggshells, regardless of media, the pH never went below 5.7. Regardless of sample type, the lowest pH was 6.1, 6.2, and 6.4 for UP, M-9, and BPW, respectively. For the pre-enrichment medium commonly used in the US, (LB) the pH dropped to 4.7 to 4.9 with broiler litter and 4.2 for boot covers used in turkey or broiler houses. Many researchers testing these sample types are unaware of this potential for pH change during pre-enrichment and may be underestimating the presence of Salmonella .